Agri-Food Supply Chains and Rural Revitalization: Implications for Land Use and Regional Development in Ghana - Obiri-Yeboah, Hanson; Odamtten, Michael; Antwi, Daniel; Nartey, Emelia Dede; Eshun, Josephine (New Countryside, 2026)
Agri-food supply chains play a critical role in shaping rural revitalization, land use, and regional development, particularly in agrarian economies where livelihoods are closely tied to land-based production systems. However, limited empirical research has examined how supply chain structures influence land use and regional development outcomes in Ghana. This study examines how agri-food supply chains support rural revitalization, shape land use practices, and contribute to regional development in Ghana. Adopting a qualitative case study design, the study focuses on selected commodity supply chains (cocoa, maize, rice, and roots and tubers) which are central to rural livelihoods and agricultural land use across Ghana's diverse agro-ecological zones. Data were collected through semi-structured interviews with key supply chain actors and complemented with analysis of policy documents and secondary sources. Thematic analysis was employed to identify recurring patterns and relationships across the data. The findings reveal significant variation in supply chain structures and governance across commodities. Well-coordinated supply chains, particularly in the cocoa sector, enhance market access, income stability, and incentives for sustainable land management. In contrast, loosely organized food crop supply chains are characterized by price volatility, weak bargaining power for smallholders, and limited local value addition. The study further finds that agri-food supply chains contribute to rural employment and regional integration but are constrained by inadequate infrastructure and processing capacity, resulting in spatial disparities in development outcomes.